Influence of dietary supplementation of modified tall oil and vitamin E on bacon characteristics - A T Waylan; P R O'Quinn; J C Woodworth; S I Koo; John A Unruh; Robert D Goodband; Jim L Nelssen; Michael D Tokach (Kansas Agricultural Experiment Station Research Reports, 1999)
Seventy-two crossbred (PIC) barrows were used to determine the influence of feeding modified tall oil (MTO, 0 or .5% of diet) and vitamin E (0, 10, or 50 IU/lb of feed) on bacon quality characteristics. Feeding MTO to pigs during both. the growing and finishing phases increased bacon slice firmness. Feeding swine MTO and vitamin E had minimal effects on bacon production, proximate analysis, and quality traits. Therefore, any of these combinations of MTO with vitamin E can be fed to swine to improve carcass traits without affecting bacon.; Swine Day, Manhattan, KS, November 18, 1999
Keywords: Swine day; 1999; Kansas Agricultural Experiment Station contribution; no. 00-103-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 841; Swine; Modified tall oil; Vitamin E; Bacon